Approximating Solutions of Matrix Equations via Fixed Point Techniques - Rahul Shukla; Rajendra Pant; Hemant Kumar Nashine; Manuel De la Sen (Mathematics, 2021)
The principal goal of this work is to investigate new sufficient conditions for the existence and convergence of positive definite solutions to certain classes of matrix equations. Under specific assumptions, the basic tool in our study is a monotone mapping, which admits a unique fixed point in the setting of a partially ordered Banach space. To estimate solutions to these matrix equations, we use the Krasnosel’skiĭ iterative technique. We also discuss some useful examples to illustrate our results.